DISCURSIVE STRATEGIES IN LIGHT OF THE COGNITIVE LINGUISTIC APPROACH: DICHOTOMOUS CONSTRUAL OF SOCIAL ROLES IN THE MEDIA AND (MESO)POLITICAL DISCOURSE. - Ninković, Lena Z. (Nasleđe, 2022)
This paper examines discursive strategies in two genres of public discourse whose common goal is the delegitimization of the other socio-political factor, ideologically opposed to the deictic center. The research was based on the cognitive-linguistic approach to discourse analysis. The corpus consists of two thematic units: the July protests (2020) (media discourse) and the relationship between the government and the opposition (2018-2021) (mesopolitical discourse). The research involves the identification of discursive strategies and a description of the underlying cognitive operations that evoke the desired content on a conceptual level. Research has shown that structural configuration and framing (metaphorization or categorization) are the most common strategies for achieving the intended effect, and that differences in ideological reproduction arise from the manipulation of entity positioning strategies in the discourse space.